A Digital escapism and stress: exploring the connection (The Journal of Psychology and Sociology, 2025)
In the digital age, media escapism has become an integral part of everyday life, often serving as ameans of coping with stress. This study aims to investigate the relationship between stress levels anddigital escapism, examining how individuals use digital media to regulate emotional states.The research highlights the psychological and practical significance of understanding digital escapismas a coping mechanism. By identifying the extent to which stress influences media consumptionpatterns, this study contributes to the broader discussion on mental health and digital behavior. Themethodology includes a quantitative approach, utilizing validated psychological scales to assess stresslevels and media escapism tendencies among participants. Statistical analysis was applied to determinecorrelations between these variables.The findings suggest a significant relationship between stress and media escapism, indicating thathigher stress levels may lead to increased engagement in digital content as a form of psychological relief.These results contribute to the growing body of knowledge on digital psychology, offering insights intothe potential risks and benefits of media escapism in stress management.The practical implications of this study lie in its relevance for psychologists, educators, and policymakersseeking to develop strategies for healthier digital consumption habits. Understanding the roleof digital escapism in stress regulation can inform interventions aimed at promoting psychological wellbeingin the digital era.Keywords: digital escapism, stress, media consumption, psychological well-being.